Ambition at work and career satisfaction: The mediating role of taking charge behavior and the moderating role of pay. Issue 1 (13th February 2017) - El Baroudi, Sabrine; Fleisher, Chen; Khapova, Svetlana N.; Jansen, Paul; Richardson, Julia
Abstract : Purpose: The purpose of this paper is to examine the moderating role of pay in the relationship between employee ambition and taking charge behavior, and its subsequent effects on employee career satisfaction. Design/methodology/approach: A two-wave quantitative investigation was conducted among alumni of a large public university in the Netherlands. Findings: The results show that taking charge behavior mediates the positive relationship between employee ambition and career satisfaction. They also show that pay positively moderates this mediation, such that the relationship between employee ambition and taking charge behavior is stronger when ambitious employees receive an increase in pay, leading to increased career satisfaction. Conversely, a decrease in pay does not moderate ambitious employees' taking charge behavior and the impact on their career satisfaction. Research limitations/implications: The study draws on self-report data collected in one country: the Netherlands. Practical implications: The study highlights the importance of pay for higher job involvement, demonstrating its impact on taking charge behavior among employees with higher levels of ambition. Originality/value: This is the first empirical study to examine the impact of pay on employees' taking charge behavior and the subsequent implications for career satisfaction.